Picture perfect - Kain, P. G. (Kain, P. G. Commercial breaks ;, 2012)
It's easy being part of a perfect family when you are in front of a camera. Every one says the right thing because it's printed on a cue card. But Cassie Herold in real life knows her parents are having problems. Can she get a date with handsome Rory Roberts and bring her family back on track?